The Influence of Circulation Patterns on Visitor Crossing Patterns at Cihampelas Walk Bandung - Sugiharti, Enok; Nawawi, Zidan; Nugraha, Rafiq (Universitas Pendidikan Indonesia (UPI), 2025)
This research aims to analyze the relationship between the spatial circulation patterns at Cihampelas Walk Mall (Ciwalk) Bandung and the movement patterns as well as the distribution of visitors within the area. The main issue in this research is how the right circulation pattern can enhance comfort, movement efficiency, and the even distribution of visitors within the shopping center area. The research was conducted using a verifiable qualitative approach through descriptive-analytical and descriptive-comparative methods. Data were collected through direct observation, interviews with managers and visitors, field documentation, and literature review of theories related to spatial circulation. The objects of study include space configuration, circulation paths, and user interactions in the indoor and outdoor areas of Ciwalk. The research results show that the circulation design at Ciwalk is linear-dynamic, formed by the arrangement of building masses that respond to the irregular site shape and the application of the open mall concept. Linear patterns are commonly found in retail areas, while open areas such as plazas and gardens exhibit dynamic circulation patterns that support movement flexibility. The presence of the skywalk, central plaza, and pedestrian pathways surrounding the main building plays a crucial role in creating meeting points for visitors and naturally directing the flow of circulation. The separation of vehicle and pedestrian paths also enhances the comfort and safety of visitors. This study concludes that a well-designed circulation pattern can optimize spatial experience, enhance the area's attractiveness, and support the sustainability of visitor activities comprehensively